Comparism Of Cryoprecipitate Production Methods Using Fibrinogen And Factor VIII Assay. (28th October 2020) - Bolarinwa, A; Otokiti, O E
Abstract: Introduction/Objective: cryopecipiitate is of huge importance in the management of some Bleeding disorders especially in a low resource settings like ours where it is still the mainstay of management of disseminated Intravsacular coagulopathy, Haemophilia and Von willebrand Disease. In this study we aimed to compared the quality of cryoprecipitate produced using the Thaw-siphon method (no centrifugation) and the ones produced using the Slow- thawing (with centrifugation) methods Methods: Ten units of newly prepared Fresh Frozen plasmas were randomly selected, five of were used to prepare cryoprecipitate using the Thaw-siphon method while cryoprecipitate were prepared using the slow-thawing plus centrifugation method. The Fibrinogen concentration in all the ten units were determined using the modified Claus tehcnique while the Factor Viii assay of each unit was done using the one-stage APTT based Assay method Results: using the Thaw-siphon method, the mean fibrinogen concentration (152mg/bag) was found to be lower than that of units prepared with slow-thawing plus centrifugation methods (256mg/bag). In a similar manner Factor Viii concentrations were higher in the Slow-thawing with centrifugation methods, Mean Factor Viii concentration was 172Iu/bag when compared with 82 IU/bag in Thaw-siphon methods Conclusion: We concluded that Cryoprecipiate produced usng the Thaw- centrifugation methods have higher Fibrinogen and factor Viii units and as such, smaller quantity will be required for correction of coagulopathy when compared with the Thaw-siphon methods. Despite this glaring and expected findings, it is worthy of note that the cryoprecipitate units produced by Thaw-siphon methods meets the required criteria for quality cryoprecipitate and will be very useful in a low resource settings.